Th17 lymphocytes traffic to the central nervous system independently of α4 integrin expression during EAE - Rothhammer, Veit; Heink, Sylvia; Petermann, Franziska; Srivastava, Rajneesh; Claussen, Malte C.; Hemmer, Bernhard; Korn, Thomas (Journal of Experimental Medicine, 2011)
The integrin α4β1 (VLA-4) is used by encephalitogenic T cells to enter the central nervous system (CNS). However, both Th1 and Th17 cells are capable of inducing experimental autoimmune encephalomyelitis (EAE), and the molecular cues mediating the infiltration of Th1 versus Th17 cells into the CNS have not yet been defined. We investigated how blocking of α4 integrins affected trafficking of Th1 and Th17 cells into the CNS during EAE. Although antibody-mediated inhibition of α4 integrins prevented EAE when MOG 35-55-specific Th1 cells were adoptively transferred, Th17 cells entered the brain, but not the spinal cord parenchyma, irrespective of α4 blockade. Accordingly, T cell-conditional α4-deficient mice were not resistant to actively induced EAE but showed an ataxic syndrome with predominantly supraspinal infiltrates of IL-23R +CCR6 +CD4 + T cells. The entry of α4-deficient Th17 cells into the CNS was abolished by blockade of LFA-1 (αLβ2 integrin). Thus, Th1 cells preferentially infiltrate the spinal cord via an α4 integrin-mediated mechanism, whereas the entry of Th17 cells into the brain parenchyma occurs in the absence of α4 integrins but is dependent on the expression of αLβ2. These observations have implications for the understanding of lesion localization, immunosurveillance, and drug design in multiple sclerosis. © 2011 Rothhammer et al.
CRIS-Team Scopus Importer:2020-09-22